A revision of the Neotropical caddisfly genus Rhyacopsyche, with the description of 13 new species (Trichoptera: Hydroptilidae) - Wasmund, Anne M.; Holzenthal, Ralph W. (Zootaxa, 2007)
The Neotropical genus Rhyacopsyche Müller, 1879, was last reviewed in 1971 when 5 species were known. Since that time, the genus has gradually grown to 13 species: R. andina Flint, 1991 (Colombia, Peru, Venezuela), R. chichotla Bueno & Hamilton, 1986 (Mexico), R. duplicispina Flint, 1996 (Tobago), R. hagenii Müller, 1879b (Argentina, Brazil, Uruguay), R. jimena Flint, 1991 (Colombia), R. matthiasi Flint, 1991 (Colombia), R. mexicana (Flint, 1967) (Costa Rica, Guatemala, Mexico, Nicaragua), R. mutisi Mey & Joost, 1990 (Colombia), R. obliqua Flint, 1971 (Mexico), R. peruviana Flint, 1975 (Ecuador, Peru), R. torulosa Flint, 1971 (Costa Rica, Guatemala), R. turrialbae Flint, 1971 (Costa Rica), and R. yatay Angrisano, 1989 (Argentina). Thirteen new species are described and illustrated: R. benwa (Bolivia, Ecuador, Peru), R. bulbosa (Brazil), R. colei (Venezuela), R. colombiana (Colombia), R. colubrinosa (Ecuador, Peru), R. dikrosa (Brazil), R. flinti (Venezuela), R. hasta (Peru), R. intraspira (Peru), R. otarosa (Venezuela), R. patulosa (Brazil), R. rhamphisa (Colombia, Costa Rica), and R. tanylobosa. (Ecuador, Peru, Venezuela). The distribution of Rhyacopsyche is widened to include Bolivia and Nicaragua. Detailed illustrations are presented for all species as well as diagnoses, descriptions, and a taxonomic key. A species level phylogenetic analysis using PAUP* 4.0b 10 was performed. A heuristic search was conducted based on 20 morphological characters of the male genitalia, with species of Ochrotrichia and Metrichia used as outgroups. A strict consensus of 23 equally parsimonious trees is presented. The analysis revealed 3 characters supporting the monophyly of Rhyacopsyche. The monophyly of 1 of the 2 previously established species groups, the turrialbae group, is supported.